Opsi KPBU Proyek SPAM Regional Keburejo Provinsi Jawa Tengah: Pendekatan Manajemen Risiko - Sutantiningrum, Kartika Hapsari; Hatmoko, Jati Utomo Dwi (Department of Civil Engineering, Diponegoro University, 2019)
To achieve the target of 100% drinking water service, Central Java Provincial Government holds regional water supply system (SPAM) programmes in Central Java, one of which is Keburejo regional water supply system (Kebumen and Purworejo). During the development phase, it was delayed due to project cost overrun, which later promotes an option for Public-Private Partnership (PPP). Consequently, this option may increase the project risks. This study aims to identify and analyze the risks of Keburejo regional water supply system project when the PPP option is chosen. This research adopted a mixed research method of qualitative and quantitative approach. Respondents in this study were 22 respondents from PDAB Tirta Utama, Dinas Bina Marga and Cipta Karya (BMCK) Central Java, Satker PSPAM Central Java, BBWS Serayu Opak, Pemkab (PDAM, Bappeda and DPU) Kebumen and Purworejo, as well as Business Entity (PT. TGM). The results found 24 risk factors, classified into pre-construction (10), construction (4), and Operational and Maintenance (10). The majority of these risks are considered ‘High’ (83.33%), with the highest risks in the pre-construction (37,5%), and the majority is under the Government responsibility (66.67%). These results are useful for Government as a reference in managing the risks of PPP SPAM Regional Keburejo and other regional SPAM projects in Indonesia.